Development and application of a curcumin-cinnamon essential oil nanoemulsion agent against mycobacteria - Lei, Zhihui; Ren, Yixuan; Wang, Jinyao; Shi, Haisu; Lin, Hu; Chen, Hong; Bi, Lijun; Wang, Yutang; Zhang, Hongtai (Frontiers in Cellular and Infection Microbiology, 2025)
With the increasing prevalence of drug-resistant Mycobacterium tuberculosis (M. tuberculosis), the development of novel anti-mycobacterial agents has become urgent. In this study, a curcumin-cinnamon essential oil (Cur-CEO) nanoemulsion was developed with optimized preparation parameters, including a 10% CEO volume fraction, 7.5 minutes of ultrasonic treatment, and 350 W ultrasound power, yielding a particle size of 101.14 nm. The nanoemulsion demonstrated high encapsulation efficiency (90.2%) and stability, with a stability coefficient of 0.984. Structural analysis revealed a dense network structure of the nanoemulsion and amorphous forms of Cur and CEO, enhanced by hydrogen bonding and electrostatic interactions, which improved solubility and bioavailability. The Cur-CEO nanoemulsion exhibited potent antimicrobial activity against mycobacteria, demonstrating MIC values of 2 µg/mL and 0.25 µg/mL against Mycobacterium smegmatis and M. tuberculosis, respectively, representing a fourfold reduction compared to the CEO solution alone, owing to its ability to induce substantial damage to mycobacterial cell membranes and consequently enhance nucleic acid and protein leakage. Furthermore, the aerosol form of the nanoemulsion effectively inhibited both surface and airborne mycobacteria, with no significant changes in structural properties post-atomization. Lung deposition studies indicated that 75.6% of aerosol particles of the nanoemulsion reached the alveolar region, suggesting its potential as an inhalation agent. Additionally, the Cur-CEO nanoemulsion exhibited negligible effects on macrophage viability, maintaining a survival rate exceeding 85% even at concentrations up to 1250 ng/mL. These findings indicate that the Cur-CEO nanoemulsion, formulated using natural ingredients, holds significant promise as a food-grade antibacterial agent for the prevention and control of mycobacterial infections.